An unusual origin of liposarcoma in an elderly man: a case report - Tseng, Chin-Lun; Wang, Jui-Ho (International Surgery Journal, 2021)
Liposarcoma is a type of cancer with mesenchymal origin in which the bulk of tumor differentiates into adipose tissue. Liposarcoma can be found in any part of the body with fat cells, but most cases occur in the muscles of the limbs or in the retroperitoneum. Here we report a case of an elderly man with an uncommon origin of liposarcoma. A 76-year-old man presented to hospital with gastrointestinal symptoms and a palpable mass over lower abdomen. Abdominal computer tomography revealed colonic tumor with another huge intraperitoneal mass, looks like originated from mesentery of small intestine. The patient underwent an exploratory laparotomy. During operation, despite colon cancer, a 17cm mass, originated from distal ileum mesentery was noted. The specimen histopathology of the tumor resection showed well-differentiated liposarcoma with prominent myxoid stroma. Finally, the patient was discharged on the tenth postoperative day. Most of liposarcomas origin from the extremities, retroperitoneum and inguinal region. However, we have chance to find liposarcomas everywhere in our body. In our case, it was a liposarcoma derived from mesentery of small intestine and it had few reports before.